Beauty Wisdom - Vyas, Bharti and Haggard, Claire (London Thorsons, 1998)
A complete and practical top-to-toe guide to holistic health and "home spa" beauty treatments. This text emphasizes both inner health and holistic therapies, including acupressure and reflexology techniques, lymphatic drainage and massage, as well as make-up, skin and haircare advice.
Include Index and Illustrations
Keywords: Beauty, Personal